Estratégias de internacionalização de negócios - André Neto, Antonio (2004)
This work results from the analysis of historical data obtained from different sources and the froin the observation that, in spite ofthe fact that Brazil had established an historical record of exports during 2003, the great majority ofthe Brazihan exporting companies do not consider the intemational commerce as a strategic goal, but a marginal operation, used to fulfill the lack of demand of the Brazjlian domestic market. This altitude rarely creates commercial ties and in most of the cases, it results in a downgrade in the image and consequently in the price of the goods, because importers seeks for quality, on time delivery and continuous sourcing. The proposition of this work is to list different strategies to internationalize the business and its step-by-step process, so that companies may use them in different stages of its efforts to develop business abroad. These strategies may help to consolidate the presence of the company as an exporter as well as its establishment as a local player in the target markets. The strategies are described in a sequence, starting from the simplest to the most sophisticated, trying to create a natural path of exposition and leaming. To support the strategies, there is a section describing the major risks and a checklist to elaborate an International Business Plan, a ver) important step to develop a long term altitude fowards the international business.